Assessment of primary healthcare accessibility and inequality in north-eastern Kazakhstan - Shaltynov, Askhat (2022)
Out of the many aspects of health care, the concept of physical accessibility is a priority that not only encompasses availability of health care resources, but also requires that they are easily accessible for all. To assess this factor as expressed in terms of the number of available physicians in the north-eastern part of Kazakhstan, we used the enhanced two-step float catchment area in a geographic information system approach. The Gini index and the Lorentz curve were used to evaluate the economic inequality within this region. Based on the data obtained, we developed models to increase the availability of health care considering allocation of additional primary health care resources. A low to zero index was found to be typical for most rural settlements, which currently make up less than 15% of the total population. We also identified a correlation between the index of accessibility and that of inequality, which indicates that areas with high accessibility show a more equitable distribution of resources. The developed location/ allocation models of additional primary health care resources can be useful in implementing government initiatives to improve the availability of primary health care in rural areas.